Ocular Autoimmune Systemic Inflammatory Infectious Study – Report 3: Posterior and Panuveitis. (2nd January 2019) - Lee, Joanne H.; Mi, Helen; Lim, Rachel; Ho, Su Ling; Lim, Wee Kiak; Teoh, Stephen C.; Agrawal, Rupesh
ABSTRACT: Purpose : To report the pattern of posterior and panuveitis at a tertiary referral center in Singapore. Methods : Subgroup retrospective analysis of 334 new posterior and panuveitis cases, from the Ocular Autoimmune Systemic Inflammatory Infectious Study (OASIS) database. Descriptive analysis was performed and visual outcome and complications were reported. Results : The etiology for posterior uveitis and panuveitis was infectious in 162 patients (48.5%), non-infectious in 144 patients (43.1%), and idiopathic in 28 patients (8.4%). More patients with bilateral disease had a non-infectious etiology ( n = 82, 50.9%) ( p = 0.012). The most common complication was epiretinal membrane ( n = 20, 12.3%) for the infectious group and cystoid macular edema ( n = 12, 8.3%) for the non-infectious group. Conclusions : The proportion of etiologies in our cohort varies from other studies. Understanding the variations and demographic associations allows the diagnosis and management of posterior and panuveitis to be further improved.